Strategic Communication Intervention to Stimulate Interest in Research and Evidence‐Based Practice: A 12‐Year Follow‐Up Study With Registered Nurses. Issue 1 (13th October 2015) - Morténius, Helena; Hildingh, Cathrine; Fridlund, Bengt
ABSTRACT: Background: Bridging the research–practice gap is a challenge for health care. Fostering awareness of and interest in research and development (R & D) can serve as a platform to help nurses and others bridge this gap. Strategic communication is an interdisciplinary field that has been used to achieve long‐term interest in adopting and applying R & D in primary care. Aim: The aim of the study was to evaluate the impact of a strategic communication intervention on long‐term interest in R & D among primary care staff members (PCSMs) in general and registered nurses (RNs) in particular. Methods: This prospective intervention study included all members of the PCSMs, including RNs, in a Swedish primary care area. The interest of PCSMs in R & D was measured on two occasions, at 7 and 12 years, using both bivariate and multivariate tests. Results: A total of 99.5% of RNs gained awareness of R & D after the first 7 years of intervention versus 95% of the remaining PCSMs ( p = .004). A comparison of the two measurements ascertained stability and improvement of interest in R & D among RNs, compared with all other PCSMs (odds ratio 1.81; confidence interval 1.08–3.06). Moreover, the RNs who did become interested in R & D also demonstrated increased intention to adopt innovative thinking in their work over time ( p = .005). Linking Evidence to Action: RNs play an important role in reducing the gap between theory and practice. Strategic communication was a significant tool for inspiring interest in R & D. Application of this platform to generate interest in R & D is a unique intervention and should be recognized for future interventions in primary care. Positive attitudes toward R & D may reinforce the use of evidence‐based practice in health care, thereby making a long‐term contribution to the patient benefit.